Shallow and intermediate depth earthquakes in the Hindu Kush region across the Afghan-Pakistan border. (15th October 2017) - Rehman, Khaista; Ali, Wajid; Ali, Asghar; Ali, Aamir; Barkat, Adnan
Graphical abstract: Highlights: Seismicity parameters of earthquakes in the Hindu Kush region are provided. Large earthquakes in a small zone of intense activity are investigated. Seismicity patterns are revealed using frequency-magnitude distribution. Zones of low b-value are identified with the intermediate depth range. Abstract: We investigated the spatio-temporal seismicity parameters of shallow (0–70 km) and intermediate (70–300 km) depth earthquakes in the Hindu Kush region, which is characterized by the occurrence of large earthquakes in a small zone of intense activity. By way of comparison, intermediate depth earthquakes dominate the Hindu Kush seismicity. Using a catalogue of 3820 earthquakes, we determined the various earthquake histograms, time-series plots, variations of frequency-magnitude distribution (b-value) and seismicity rate changes (z-value). Both time periods, encompassing pre- and post-1964 subsets of earthquakes, differ significantly in terms of reporting earthquakes, b- and z-value for shallow and intermediate seismicity. The b-values appear to be lower (1.07 and 0.90) for intermediate depth earthquakes than do the b-values produced by shallow earthquakes (1.32 and 1.06) using the pre- and post-1964 data sets. The three low b-value (<0.9) areas have been identified within the intermediate depth seismicity region of the Hindu Kush. The z-value maps show that the earthquakes with magnitude of 7.0 and above can only be seen in the intermediate depth earthquake maps.